Kelemahan Negara dalam Pelanggaran APK Pemilu Serentak 2019 Kota Denpasar - Shah, Irfan; Putra Erawan, I Ketut; Mahaswari J.M, A.A.Sagung Mirah (Jurnal Nawala Politika, 2019)
ABS TRACT   T his r esearch a i m ed t o d etermine the f actors behind the poor r esponse of the s tate t o the c ampaign props v i olations i n Denpasar City. A s the r e s earch framework, this r esearch used the s tate i n s ociety t heory a nd c ollective action theory. T his r esearch used the c ase s tudy method. T he findings r e presented t hat p olitical p ower i n v arious government i nstitutions was the r e ason behind the s tate’s w eakness i n overcoming the c ampaign props v i o l ations. T hrough i mages and practices i n the c ampaign props phenomenon, i t c an be s een that the r elationship between the s tate and political parties was c aused by the transformation of s ociety through political p arties for the purpose of d omination. C onditions cr eated by t he i mages, practices, a nd t r ansformations l ed to v arious i m pacts, from c ollective action i n political p arties to t he occurrence of free ri ders by political parties i nside a nd o utside t he c oalitions, which i ncreased   the n umber of c a mpaign props v i o l ations.   Key Words:  Campaign prop violations, Election Supervisory Board, Political parties, Denpasar